MEDIA PEMBELAJARAN PENGENALAN HURUF HIJAIYAH UNTUK ANAK USIA DINI 2-3 TAHUN - Lisna Zahrotun (Jurusan Teknik Informatika, 2015)
Learning media are nothing new in the world of education. Many schools are already introducing computers in the learning process. The images and sounds that appear also makes children do not get bored quickly, so it may stimulate children to know more. In addition to computer-based learning children can learn to perform the mouse movements that can train the child's motor.In this study produced teaching media literacy hijaiyah which is one of the curriculum for the education of children aged 2-3 years. Instructional media is equipped with voice pronunciation pronunciation of letters hijaiyah. In addition to learning media is also equipped with a guessing menu that is divided into two levels. With the child's learning media is expected to be able to make the process of learning to know the letters hijaiyah accompanied by sound pronunciation can be happy with no load and coercion from teachers.Learning mediaare nothing newin the world ofeducation. Manyschoolsarealreadyintroducingcomputersin the learning process. The imagesand soundsthat appearalso makeschildren do notget bored quickly,so itmaystimulate childrento know more. In additiontocomputer-based learningchildren canlearn toperformthe mouse movementsthatcantrain thechild's motor.In this studyproducedteaching medialiteracyhijaiyahwhichis one of thecurriculumfor the education ofchildren aged2-3 years. Instructional mediais equipped withvoicepronunciationpronunciationof lettershijaiyah. In additiontolearning mediais also equippedwitha guessingmenuthat is dividedintotwolevels.With thechild'slearning mediais expected tobe able tomake the process oflearning to knowthe lettershijaiyahaccompaniedbysoundpronunciation can be happywith no loadandcoercionfromteachers.